Janice VanCleave's rocks and minerals : mind-boggling experiments you can turn into science fair projects - VanCleave, Janice Pratt; Ettlinger, Doris (New York : Wiley, 1996)
Twenty fun and simple experiments, using inexpensive household materials, that reveal the properties of rocks and minerals, with suggestions for developing science fair projects.
"Science for fun"--Cover.
Includes bibliographical references (p. 84) and index.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
6.7.
Keywords: Minerals -- Experiments -- Juvenile literature; Rocks -- Experiments -- Juvenile literature; Experiments; Minerals -- Experiments; Rocks -- Experiments; Science projects; Minerals -- Experiments; Rocks -- Experiments; Science projects; Science -- Experiments